Development of Android-Based E-Comic as a Learning Media for Pancasila Education to Improve Learning Outcomes for Class V Elementary Schools - Elsa Nasywa Charisa; Moh Fathurrahman (Universitas Negeri Malang, 2025)
Abstract: Improving student learning outcomes through the use of learning media is the focus of research, which also highlights the importance of recent innovations in this field. This research uses the research and development (R&D) method with the ADDIE model, which includes: analysis, design, development, implementation, and evaluation. The subjects of this research were twenty-four fifth-grade students from Pati Regency. The results of observations, interviews, questionnaires, and documentation were used to collect data. Data analysis techniques include feasibility tests, product validity tests, data normality tests, and paired sample t-tests. Media and material validation resulted in an average score of 94.37%, placing it in the